Pembuatan Karakter Animasi “Halo Saya Disabilitas” untuk Memperkuat Isu Disabilitas pada Sektor Pendidikan - Hadiprawiro, Yulianto; Susanti, Dewi Indah; Hidayati, Atiek Nur; Saptodewo, Febrianto; Dawami, Angga Kusuma (Presisi Jurnal Pengabdian Masyarakat, 2023)
The issue of disability in the education sector still has not had much influence on changing the stigma towards Children with Special Needs (ABK) with disabilities in the education sector. Through the animated characters in the service "Hello I am disabled" it is an effort to understand the personal character of people with disabilities in the school education sector. This paper uses a descriptive-qualitative perspective on the process of creating animated characters for the animation "Hello I'm Disabled". The result of this paper is a process of dedication to the form of animated characters that have a strong identity in displaying visual constructions with depictions of disabilities.